2022
DOI: 10.1128/spectrum.00533-22
|View full text |Cite
|
Sign up to set email alerts
|

Study of Wetland Soils of the Salar de Atacama with Different Azonal Vegetative Formations Reveals Changes in the Microbiota Associated with Hygrophile Plant Type on the Soil Surface

Abstract: The study of the composition and diversity of the wetland soil microbiota associated with hygrophilous plants in a desert ecosystem of the high Puna in northern Chile makes it an ideal approach to search for novel extremophilic microorganisms with unique properties. These microorganisms are adapted to survive in ecological niches, such as those with high UV irradiation, extreme drought, and high salt concentration; they can be applied in various fields, such as biotechnology and astrobiology, and industries, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 117 publications
2
1
0
Order By: Relevance
“…One interesting component of the microbiota composition in the La Punta–La Brava system lake is the presence of Archaea, such as Thermoplasmatota and Crenarchaeota , belonging to the phylum Euryarchaeota ( 43 ). This phylum was present in other sediment lake studies in Canada ( 44 ) and Switzerland ( 45 ) and has been found in previous studies in soils of the same area related to native vegetation ( 46 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…One interesting component of the microbiota composition in the La Punta–La Brava system lake is the presence of Archaea, such as Thermoplasmatota and Crenarchaeota , belonging to the phylum Euryarchaeota ( 43 ). This phylum was present in other sediment lake studies in Canada ( 44 ) and Switzerland ( 45 ) and has been found in previous studies in soils of the same area related to native vegetation ( 46 ).…”
Section: Discussionsupporting
confidence: 83%
“…3 ). In comparison with sediment samples from other studies, the composition of the microbiota is similar, including Archaea found in the La Punta–La Brava lake system ( 40 , 44 , 45 ), and is more similar to lakes with a high influence of seawater ( 60 ), owing to the high salt content present of the La Punta–La Brava lake system.…”
Section: Discussionsupporting
confidence: 48%
“…Rio Tinto (SW Spain) is a popular site for astrobiological research since microbial communities live in acidic environments in this location [ 137 ]. Similarly, references in this cluster are given to the Salar de Atacama (Chile), investigated as a dry desert with high levels of UV irradiation and salt concentration [ 138 ]. The red stone of the Salar de Atacama Desert displays a substantial occurrence of sulfate-reducing bacteria, cyanobacteria, and other “microorganisms” with unique genetic sequences that are not phylogenetically classifiable and displays a peculiar lipid “biosignature” [ 112 , 128 ].…”
Section: Discussionmentioning
confidence: 99%